MENINGKATKAN KREATIVITAS ANAK USIA DINI MELALUI PEMBUATAN ALAT PERMAINAN EDUKATIF (APE) - Laili, Rahmania Alfi; Mintarsih, Mintarsih; Masrurroh, Mi’rotin Barro; Astuti, Mardiana Dwi; Susanti, Mei Tri (Jurnal Penamas Adi Buana, 2017)
Games Education (APE) is a tool that can optimize the game development of the child, tailored to the age and developmental level, and which is useful for the development of the physical, language, cognitive, and social development. The purpose of this activity is expected in early childhood and kindergarten students get an interesting experience, increase cognitive ability, psychomotor, and creative both in school and outside of school. Berbagia type of form tool of education games that can be made by children TK and early childhood education. This education game is used as a medium of learning so that students do not feel bored while studying. Type of APE are so numerous, yitu playdough, finger painting, hand puppets, and coloring. The method used in this activity is practical. By using this method the children can directly try to make a toy that kids can feel the process of making. The target of this education a children’s game kindergarten and early childhood. However, given the different game types for different ability levels, especially in terms of cognitive and psychomotor. Tools are provided for educational games help improve a child’s development in terms of skills, knowledge, and dissemination in accordance with the learning materials. Of the activity of making APE results obtained are kindergarten and early childhood was happy to make the game instrument itself, creativity and children honed so well that it can blind a variety of forms. Keywords : Games, Education, Develompent, Children